MANFAAT AKTIVITAS FISIK TERHADAP REGENERASI MENTAL DAN PEMBENTUKAN KARAKTER SISWA: TINJAUAN LITERATUR - Mahmudah Mahmudah (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study examines the benefits of physical activity on mental regeneration and character building in students based on a literature review. The results of the study indicate that physical activity plays an important role in improving students' mental health, including reducing stress and anxiety levels and improving mood and emotional well-being. In addition, physical activity also contributes significantly to character building in students, such as developing values of discipline, cooperation, sportsmanship, and social skills. The integration of physical activity into the school curriculum and extracurricular activities is described as an important step in supporting students' holistic development, ensuring they reap the benefits of mental regeneration and character improvement. Support from educators, parents, and the community is necessary to create an environment that encourages regular physical activity, enabling students to better face academic challenges and become physically and mentally healthy individuals.